Indoor VLC system based on tri color laser diodes, dual polarization states, and OAM beams - Mehtab Singh; Somia A. Abd El-Mottaleb; Ahmad Atieh; Hassan Yousif Ahmed; Medien Zeghid; Kottakkaran Sooppy Nisar (Alexandria Engineering Journal)
This paper introduces a novel high-speed Visible Light Communication (VLC) system capable of transmitting data rates of 120 Gbps. The system leverages the multiplexing capabilities of Dual Polarization (DP) and Orbital Angular Momentum (OAM) beams. It incorporates three Laser Diode (LD) sources operating at distinct wavelengths: red (700 nm), green (570 nm), and blue (450 nm). Each LD source generates four OAM beams operating at DP states, with each OAM beam carrying a data rate of 5 Gbps. The proposed system is designed for indoor VLC applications, considering line-of-sight (LoS) link configurations. The proposed system is evaluated for different detector surface areas, and transmission distance. The bit error rate (BER), and eye diagrams as evaluation metrics are used to characterize the performance of the system. The findings of different detection areas reveal that larger surfaces yield superior performance, with significant reductions in BER observed at the cost of collecting more ambient noise. Additionally, shorter transmission distances exhibit enhanced performance, underscoring the importance of propagation range in VLC systems. Through extensive performance analysis, our proposed DP-OAM-VLC model achieves an overall transmission capacity of 120 Gbps at a range of 1.1 m, with a BER below 10−3.